Analysis Of Factors That Influence The Level Of Welfare Through Social Assistance In Rambipuji Village, Jember Regency - Destia Purnama Sari, Trya Dara; Wahyudi, Farid (Majalah Ilmiah DIAN ILMU, 2024)
This study aims to determine the effect of age, health, household income, number of family dependents on the level of family welfare of beneficiaries through the intervening variable achievement of social assistance programs. The method used is quantitative descriptive research. The population in this study was KPM (beneficiary family) from 64 social assistance programs in Rambipuji Village. Sampling uses probability samples because it provides the same opportunity to be used as a sample with simple random sampling. Data analysis techniques to answer the hypothesis in this study use the path analysis method.